Severe infective endocarditis with systemic embolism due to community associated methicillin-resistant Staphylococcus aureusST630 - Zheng,Beiwen (2015)
Community-associated methicillin-resistant Staphylococcus aureus(CA-MRSA) are increasingly causing infective endocarditis over the past decade. Here we report a healthy man who developed a severe acute infective endocarditis with systemic embolism caused by CA- MRSA. The strain was recovered from repeated blood cultures and was characterized using molecular detection and genotyping. The S. aureusisolate was typed as ST630 SCCmecV with spa-type t4549, agrI/IV and was PVL-negative. This is the only case report, to our knowledge, of CA-MRSA infective endocarditis in China. This case highlights the emergence and geographical spread of life-threatening CA-MRSA infection within China.